2015
DOI: 10.1002/jbm.b.33576
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid/carboxymethyl cellulose directly applied to transected nerve decreases axonal outgrowth

Abstract: Neuroma management is an unresolved problem. Biomaterials to limit unwanted axonal growth could be a tool to manage neuroma. Hyaluronic acid/carboxymethyl cellulose (HA/CMC) is an antiadhesive, biodegradable material that is nontoxic to nerve. The purpose of this study was to evaluate the efficacy of this biomaterial to limit axonal growth. Rats received a sciatic nerve transection and repair with a short conduit (5 mm) containing HA/CMC, fibrin, or nothing (empty conduit). In another study, nerve was transect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In addition, HA-carboxymethylcellulose solutions improve nerve regeneration and reduce perineural scar formation and adhesion after sciatic nerve repair [70]. It has been confirmed that direct application of HA-carboxymethylcellulose in transected nerves may limit axonal outgrowth by contact with regenerating axons; therefore, HAcarboxymethylcellulose barriers may prove to be a tool to prevent neuroma formation through inhibiting axonal growth [71]. On the contrary, according to some other studies, the role of HA solution in axonal outgrowth is dose-dependent, because high dose of HA (100-1000 μg/ml) topically used is characterised by significantly increased axonal outgrowth compared with HA solution (10 μg/ml) applied in the control group, in which axonal outgrowth did not occur [72].…”
Section: Hyaluronic Acidmentioning
confidence: 94%
“…In addition, HA-carboxymethylcellulose solutions improve nerve regeneration and reduce perineural scar formation and adhesion after sciatic nerve repair [70]. It has been confirmed that direct application of HA-carboxymethylcellulose in transected nerves may limit axonal outgrowth by contact with regenerating axons; therefore, HAcarboxymethylcellulose barriers may prove to be a tool to prevent neuroma formation through inhibiting axonal growth [71]. On the contrary, according to some other studies, the role of HA solution in axonal outgrowth is dose-dependent, because high dose of HA (100-1000 μg/ml) topically used is characterised by significantly increased axonal outgrowth compared with HA solution (10 μg/ml) applied in the control group, in which axonal outgrowth did not occur [72].…”
Section: Hyaluronic Acidmentioning
confidence: 94%
“…[71] HA-carboxymethyl cellulose was proved by Agenor et al to prevent aberrant outgrowth of regenerating axons, thus avoiding painful neuroma formation. [72] Citicoline Together with choline and cytidine, its metabolites, citicoline represents a substrate for phosphatidylcholine, a primary component of neuron membrane. Citicoline is a membrane stabilizer, reducing membrane breakdown and toxic products secondary to ischaemia.…”
Section: Melatoninmentioning
confidence: 99%
“…3 For many years, autologous sources were the best solution for restoration of small diameter neural tissue lesions due to biocompatibility, lack of toxicity, transmission of disease, and stimulation of cell growth. Cellular matrices with unidirectional pores, 10,11 conduits, 12 and oriented fibers 13 [15][16][17][18][19][20] Collagen, major component of ECM, is a biocompatible and biodegradable protein that promotes regeneration process. 4 Therefore, scientists tend to use synthetic scaffolds for simulation of extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have shown the positive effects of collagen, olibanum, gelatin, fibronectin, hyaluronic acid, and so on in the regulation of cell attachment, axonal regeneration, and extension as well as restoration of injured nerves. [15][16][17][18][19][20] Collagen, major component of ECM, is a biocompatible and biodegradable protein that promotes regeneration process. Its ability to stimulate axonal extension and release the smallest amount of pathogen has made collagen favorable for neural repair.…”
Section: Introductionmentioning
confidence: 99%